ANALISIS KEPUASAN PENGGUNA WEBSITE PERPUSTAKAAN MENGGUNAKAN STRUCTURAL EQUATION MODELLING (SEM) - Trisna Silvia; Zainudin Ismail; Muhamad Akbar (Jurnal Bina Komputer, 2019)
The benefits of an internet website will not achieve maximum results if students or lecturers as consumers of the Library website feel dissatisfied with the service. This study aims to test the model that describes the satisfaction of students and lecturers when using the Library website as a supporter face-to-face lecture. This research is based on the method used frequently by the previous researcher that is structural equation modeling (sem). This research was conducted in Perguruantinggi Stie Mura Lubuklinggau. The data of 100 respondents of students Classified from students and lecturer Dect and Structural Equation Modeling used to test the hypotheses of the wesbite library service characteristics, the motivation to use the website and culture using the internet to customer satisfaction.